Pengembangan Bahan Ajar Konsep Diferensial Berbasis Konflik Kognitif - Wahyu Setiawan; Veny Triyana Andika Sari (Universitas Hamzanwadi, 2018)
The purpose of this study is to assess the validity and practicality of teaching materials in the form of RPP and LKS. This type of research is research and development (R D) with the design of teaching materials (prototype), interview guides (in-depth-interview), observation sheet, where the subject is a school student in one of high school in Cimahi city. Research data were collected through diagnostic tests, evaluation tests, interviews, and observations. The research results consist of three aspects. The first aspect of validity: validator assessment of refined product obtains criteria very valid for RPP and TKM, while for LKS fulfill valid criteria. The two elements of practicality according to the teacher and student ratings: RPP, LKS, and TKM as a whole acquire possible and practical criteria. The three aspects of instructional learning: the percentage of learning activities at the second and third meetings has reached 70.56% with reasonably practicable criteria.